2013
DOI: 10.1111/cdev.12111
|View full text |Cite
|
Sign up to set email alerts
|

Majority Children's Evaluation of Acculturation Preferences of Immigrant and Emigrant Peers

Abstract: Using an experimental design, native majority group children (8-13 years, N = 842) evaluated acculturation strategies (assimilation, integration, and separation) adopted by immigrant and emigrant peers. There were medium to large effects of the perceived acculturation strategies on children's peer evaluations. Overall, assimilation was valued most, followed by integration and separation. These effects were in part mediated by perceived national belonging. In addition, the effects were stronger for lower status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 75 publications
2
26
0
1
Order By: Relevance
“…Turkish identity is a positive predictor, and mainstream identity a negative predictor, of language value and preference in Turkish immigrants to various countries (Yagmur & van de Vijver, 2011). Higher compared to lower national identification in Dutch children predicts more positive attitudes toward Turkish and Chinese peers who assimilated to Dutch culture than toward peers who preferred separation (Verkuyten et al, 2013): Higher identifying children are more concerned about identity threats (Nesdale, Maass, Durkin, & Griffiths, 2005; Pfeifer et al, 2007), and so higher identifiers are more positive about emigrants who prefer separation from Turkish culture and integration and assimilation with Dutch culture.…”
Section: Specificity Principle: Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…Turkish identity is a positive predictor, and mainstream identity a negative predictor, of language value and preference in Turkish immigrants to various countries (Yagmur & van de Vijver, 2011). Higher compared to lower national identification in Dutch children predicts more positive attitudes toward Turkish and Chinese peers who assimilated to Dutch culture than toward peers who preferred separation (Verkuyten et al, 2013): Higher identifying children are more concerned about identity threats (Nesdale, Maass, Durkin, & Griffiths, 2005; Pfeifer et al, 2007), and so higher identifiers are more positive about emigrants who prefer separation from Turkish culture and integration and assimilation with Dutch culture.…”
Section: Specificity Principle: Peoplementioning
confidence: 99%
“…The effects of acculturation on peer liking depend in part on perceived host national belonging, vary across immigrant groups, relate to intergroup contexts rather than to migration per se, and differ for high versus low national identifiers (Verkuyten et al, 2013). …”
Section: Terms Of the Specificity Principle Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to manipulate the naturalization applicant's degree of heritage culture maintenance, we used the vignette method (Van Acker & Vanbeselaere, ; Verkuyten et al, ). Each participant was exposed to the bogus Commission Report of a male immigrant from Kosovo.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, Jasinskaja‐Lahti et al () have found that host nationals perceive dual citizens (i.e., immigrants holding double allegiance with both the host country and the country of origin) as more disloyal towards the host nation than naturalized citizens who renounced their previous nationality (see also Kunst et al, ; Levy, Saguy, Halperin, & van Zomeren, ). In contrast to those who seek to maintain their heritage culture, naturalization applicants who decide to shed their former markers of cultural affiliation are indeed seen as exclusively valuing the host nation, thereby truly becoming “one of us” (Kunst & Sam, ; Verkuyten, Thijs, & Sierksma, ). In other words, when naturalization applicants seek to maintain their heritage culture, majority members should perceive them as weakly attached to the host nation.…”
Section: Introductionmentioning
confidence: 99%